Legal Consequences for House Ownership Credit (KPR) Debtors Related to Certificates That Have Not Been Transferred to Their Name Until The Credit Has Been Paid Off - Munthe, Duma Sinta Uli; Rahayu, Mella Ismelina Farma (Law Development Journal, 2024)
In everyday life, humans need a place to live as one of the three basic needs to support their lives. Humans need a house as a shelter to provide a sense of security. The 1945 Constitution of the Republic of Indonesia also guarantees the fulfillment of a decent and healthy place to live for everyone. However, not everyone has the financial ability to buy a house, so banks are present as an alternative that offers assistance facilities in the form of Home Ownership Credit (KPR). In practice, KPR transactions do not always run smoothly, sometimes there are obstacles or disputes faced by the parties. One of them is when the debtor has paid off his credit at the bank but the debtor has not received a certificate for the assets that have been paid off for years. The causes vary, one of which is because the name has not been changed on the certificate. This certainly has a detrimental impact on the debtor. This study discusses the legal consequences for KPR debtors who have paid off their KPR installments but the certificate is still not in the hands of the debtor. In the context of civil law, a certificate is valid evidence and provides legal certainty regarding a person's ownership of their property. The research method used is normative juridical by referring to the laws and regulations in force in Indonesia. The research was conducted by means of a literature study of secondary data sources. The results of the study indicate that certificates that have not been submitted to debtors because they have not been transferred can be detrimental to debtors legally because the debtor does not have legal certainty over the land he has purchased so that the debtor can request compensation and accountability from the developer and bank in accordance with the provisions of laws and regulations, especially Law No. 8 of 1999 concerning Consumer Protection.